Analysis of metabolites in green tea during the roasting process using non‐targeted metabolomics. (11th August 2022) - Liu, Fei; Tu, Zheng; Chen, Lin; Lin, Jiazheng; Zhu, Hongkai; Ye, Yang
Abstract: BACKGROUND: Roasting plays an important role in the formation of flavor of roasted green tea; however, the changes in chemicals during this process have not been systematically studied until now. To reveal the dynamic changes in chemicals in green tea during roasting, non‐targeted metabolomics, coupled with chemometrics, was employed. RESULTS: A total of 101 non‐volatile metabolites were identified in tea samples, and 29 metabolites were identified as characteristic metabolites of roasting. A significant increase in catechins and their derivatives, organic acids, and flavonoid glycosides was observed, while the content of some amino acids and their derivatives decreased over 50% during roasting. The content of theanine glucoside increased dramatically (by 21.23‐fold at the roasting stage), and Maillard‐derived compounds also increased to varying degrees. CONCLUSION: Glycosylation, oxidative polymerization, and pyrolysis were important reactions responsible for the formation and transformation of flavor compounds in roasted green tea during roasting. © 2022 Society of Chemical Industry.